Analisis Faktor-Faktor Yang Mempengaruhi Loyalitas Pelanggan Produk Sim Card Flexi Trendy Pada PT. Telkom Di Kota Bandar Lampung - Toton TOTON; Addela Sukma (Universitas Bandar Lampung (UBL), 2012)
Problems faced by PT. Telkom as the telecommunications company is the number of consumer complaints against service quality flexi users has increased every year. On the other hand the number of consumers has increased flexi users. The problem of this study is: Does Quality of Service effect on customer loyalty flexi user? The purpose of this study to determine the effect of service quality on customer’s loyalty flexi at PT. Telkom in Bandar Lampung. Sampling method used was accidental sampling as many as 78 samples. Methods of data collection using a questionnaire with Likert scale measurement. The analysis tool used is the method of multiple linear regression. The results showed that the quality of service that consists of realibility ( ), Responsiveness ( ), Assurance ( ), Empathy ( ), Tangible ( ), in this way they make positif influence where similarity regresi Y = -12,538 + 0,245X1 0,256X3 +0,325 + X2 + + 0,330X4 0,484X5. Effect of quality of service (realibility, responsiveness, assurance, empathy and tangibles) on customer loyalty (Y) with the coefficient of determination (R Square) by 0,692 means that customer loyalty can only be explained by reliability, responsiveness, assurance, empathy and tangibles statistically by 69,20% .. While the remaining 30.80% is influenced by other factors. F test results obtained F count (table Anovab) of 32,417. While the F table. obtained 2,45. Thus Ho is rejected and Ha accepted. It can be concluded that the five variables of service quality (reliability, responsiveness, assurance, empathy and tangibles) jointly have a positive and significant impact on customer loyalty.